Measurements of the impact of carbon monoxide on the performance of passive autocatalytic recombiners at containment-typical conditions in the THAI facility. (15th June 2020) - Freitag, M.; von Laufenberg, B.; Colombet, M.; Klauck, M.
Highlights: Passive autocatalytic recombiner tests performed in technical scale containment facility. Evaluation of influence of carbon monoxide on PAR performance. PAR exposed to oxygen starvation impacts hydrogen but not carbon monoxide conversion. PAR ignition limit is shifted to lower hydrogen concentration if carbon monoxide is present. Catalytic recombination of carbon monoxide in absence of hydrogen under late phase temperature. Abstract: Passive autocatalytic recombiners (PARs) have become one of the primary measures to mitigate the hydrogen risk for severe accidents in current and advanced water-cooled nuclear power plants (NPPs). The pgm (platinum group metals) coating of the catalyst inside the PAR is capable to oxidize hydrogen into water vapor as well as to convert carbon monoxide into carbon dioxide. The optimal efficiency of conversion requires a significant surplus of oxygen compared to the stoichiometric oxidization. A test series under containment typical boundary conditions was performed in the THAI facility (Thermal-hydraulics, Hydrogen, Aerosols and Iodine) to investigate the PAR performance under the presence of carbon monoxide. Ratios of injection mass flow rates of hydrogen and carbon monoxide into the test facility are investigated between 4:1 and 7:1, based on hypothetical release of CO by the molten core concrete interaction (MCCI). The findings are related to database on PAR performance carried out in previous OECD/NEA projects, THAI (2007–2009), THAI-2 (2011–2014), and THAI-3 (2016–2019). Special emphasis is placed on the investigation of the PAR under conditions of oxygen starvation, taking also into account a potential PAR poisoning by carbon monoxide, and under potential PAR induced ignitions at elevated hydrogen and carbon monoxide concentrations.